Structure, functional regulation and signaling properties of Rap2B - QU, DEBAO (Oncol Lett, 2016)
The Ras family small guanosine 5′-triphosphate (GTP)-binding protein Rap2B is is a member of the Ras oncogene family and a novel target of p53 that regulates the p53-mediated pro-survival function of cells. The Rap2B protein shares ~90% homology with Rap2A, and its sequence is 70% identical to other members of the Rap family such as RaplA and RaplB. As a result, Rap2B has been theorized to have similar signaling effectors to the GTPase-binding protein Rap, which mediates various biological functions, including the regulation of sterile 20/mitogen-activated proteins. Since its identification in the early 1990s, Rap2B has elicited a considerable interest. Numerous studies indicate that Rap2B exerts specific biological functions, including binding and stimulating phospholipase C-ε and interferon-γ. In addition, downregulation of Rap2B affects the growth of melanoma cells. The present review summarizes the possible effectors and biological functions of Rap2B. Increasing evidence clearly supports the association between Rap2B function and tumor development. Therefore, it is conceivable that anticancer drugs targeting Rap2B may be generated as novel therapies against cancer.